Decolonisation of the curriculum through the integration of indigenous knowledge in higher education - Makokotlela, M. V.; Gumbo, M.T. (South African Journal of Higher Education, 2025)
Recently there has been increased research interest in the decolonisation of the curriculum in higher education. Indigenous knowledge (IK) is the key aspect through which the curriculum in higher education can be decolonised to ensure its relevance to indigenous students and expose non–indigenous students to alternative forms of knowledge. This phenomenological study explored the decolonisation of the Environmental Education (EE) module in the Bachelor of Education Honours through integrating IK at the University of South Africa (Unisa) through interpretive paradigm and sociocultural theory. The study engaged document analysis and participant observation. Data was analysed and relevant themes were formed. The findings revealed that the University’s Strategic Plan drives decolonisation of the curriculum; the integration of IK was more evident in Tutorial Letter (TL) 102 of the EE module; there was minimal evidence of the integration of IK in TL105; IK was almost absent in TLs101, 104 and 103; and IK was only minimally introduced later in TL101 through the glossary of translated terms into African languages. The study contributes to attempts to decolonise the curriculum in higher education.